Media Literacy as a Tool in the Agency Empowerment Process - Valdmane, Liene (Acta Paedagogica Vilnensia, 2016)
The contemporary education paradigm determines the transition from the investment aspects (duration, place, teaching methodology) towards the learning outcomes closely linked to active, experiential learning, which substantiates the necessity for new types of partnership – for instance, the involvement of social partners, as well as the promotion of new types of cooperation between schools and families. A person who is able and willing to be involved in the social processes, who is capable to put forward his/her own goals and achieve these goals in a flexible manner, while adjusting to the situation and using the available resources, is the outcome of learning and may be defined as the agent. The science of pedagogy has got involved in the research on social agency in order to construct its scientific interpretation of the necessity to change the way of pedagogical thinking – namely, to direct the pedagogical discourse of moral obligation towards the cooperative model, putting emphasis on the learner as a person whose personal viewpoint is to be respected, and not as an individual who does not comprehend what he/she is doing. It is the mutual respect, rather than obedience, which is the goal of education and upbringing in the post-modern environment. Rapid technological developments have impacted the interpretation of the concept of education and the roles of the educator and the learner, putting forward each agent’s responsibility for life-long learning as a self-guided process and respecting the competences of each agent involved in education, all the while promoting their cooperation. This paper explores media literacy as the key component of agency and describes the mechanism of agency empowerment through the media education process, in an effort to find answers to the following questions: What is the key aim of media education? What is the content of media education? How media education ought to be integrated in the didactics of pedagogy and the teaching/learning process?
Keywords: agency; agent; media literacy; empowering agency